Analysis of urban heat island in Kochi, India, using a modified local climate zone classification - George Thomas; Sherin A.P; Shareekul Ansar, E.J; Zachariah (Procedia Environmental Sciences, 2014)
rban Heat Island (UHI), a measure of the near surface air temperature contrast between urbanised and adjoining rural areas, is the most pronounced effect of urbanisation. The definition of ‘urban’ varies in different contexts, which makes it difficult for direct comparison between cities in different regions. Local climate zone (LCZ) classification based method was adopted in Kochi in Southern India to study its UHI. Twelve mobile surveys were carried out from January 2011 to March 2013 to quantify UHI intensity. Pre-dawn UHI there was more intense than early night UHI, and its intensity in winter was stronger than in summer. UHI observed during winter were 4.6 o C and 3.7 o C in pre- dawn and early night respectively. The study area was classified into ten different local climate zones based on the standard zone properties. Thermal gradient between different zones and cooling rates observed in these zones were computed, which validates the LCZ classification. Maximum intensity was seen in Compact Midrise zones which cover the central part of the city. Most intense cooling was observed in openset and sparsely built regions in all seasons. Standard zone properties alone were inadequate to explain variation of UHI intensity of same classes with different surface area and diverse adjacent zones. Two more zone properties, radial distance to adjacent zone called Zone Boundary Distance, and the Nearest Adjacent Zone, are proposed here to overcome this. The use of these additional parameters gives a better understanding of the intra zone variation of UHI intensity of the same classes with different coverage area and diverse adjacent zones.